Caretakers’ understanding of malaria, use of insecticide treated net and care seeking-behavior for febrile illness of their children in Ethiopia - Birhanu, Zewdie (BMC Infect Dis, 2017)
BACKGROUND: Local understandings of malaria and use of preventive measures-are critical factors in sustained control of malaria. This study assessed caretakers’ knowledge on malaria, use of Long Lasting Insecticide Treated Nets (LLINs) and care-seeking behavior for their children’s illness in different malaria transmission settings of Ethiopia. METHODS: Data were collected from 709 caretakers of children of 2–9 years of age during in 2016. A standard questionnaire was used to assess caretakers’ perceptions of malaria, use of LLIN and care seeking behavior for febrile illness of children aged 2–9 years. RESULTS: The caretakers recognized malaria mostly by chills (70.4%, 499/709), fever (45.7%, 324/709) and headache (39.8%, 282/709). Overall, only 66.4% (471) of the caretakers knew that mosquito bite caused malaria and that it was quite heterogeneous by localities (ranging from 26.1% to 89.4%) and altitude (p < 0.05). Majority, 72.2% (512), of the caretakers knew that sleeping under LLIN could prevent malaria. Overall knowledge on malaria (mean = 51.2%) was very low with significant variations by localities, altitude and levels of malaria transmission, being low in high altitude and low in transmission areas (p < 0.05). Four hundred ninety-one (69.3%, 491/709) of the children slept under LLIN in the previous night. Of malaria related knowledge items, only knowledge of LLIN was associated with net use; non-use of LLN was higher among caretakers who did not know the role of LLIN (AOR = 0.47, 95%CI: 0.28–0.77, p = 0.003). Of course, attributing causation of malaria to stagnant water discouraged use of net (p = 0.021). Of febrile children (n = 122), only 50 (41.0%) sought care with only 17 (34.0%) seeking the care promptly. There was no significant link between knowledge of malaria and care seeking behavior (p > 0.05). However, knowledge of malaria had some level of influence on treatment source preference where caretakers with greater knowledge preferred pharmacy as source of care. CONCLUSIONS: The findings demonstrated that caretakers’ understanding of malaria was unsatisfactory with marked heterogeneity by localities. The present evidence suggests that knowledge is not sufficient enough to drive LLIN use and care seeking. Yet, context-specific health education interventions are important besides ensuring access to necessary preventive tools.